Phân tích đa thức (x + y + z)2 + (x + y – z)2 – 4z2 thành nhân tử, ta được A. (x + y + z)(x + y – z); B. 2(x + y + z)(x + y – z); C. (x + y + z)(x + y – 2z); D. (x + y + z)(2x + 2y – z).

Phân tích đa thức (x + y + z)2 + (x + y – z)2 – 4z2 thành nhân tử, ta được

A. (x + y + z)(x + y – z);
B. 2(x + y + z)(x + y – z);
C. (x + y + z)(x + y – 2z);
D. (x + y + z)(2x + 2y – z).

Trả lời

Đáp án đúng là: B

(x + y + z)2 + (x + y – z)2 – 4z2

= (x + y + z)2 + [(x + y – z)2  – 4z2]

= (x + y + z)2 + [(x + y – z)2  – (2z)2]

= (x + y + z)2 + (x + y – z – 2z)(x + y – z + 2z)

= (x + y + z)2 + (x + y – 3z)(x + y + z)

= (x + y + z)[(x + y + z) + (x + y – 3z)]

= (x + y + z) [x + y + z + x + y – 3z]

= (x + y + z)(2x + 2y – 2z)

= 2(x + y + z)(x + y – z).

Câu hỏi cùng chủ đề

Xem tất cả